Severe Calcification of the Ascending Aorta Detected Incidentally in Patients Undergoing Cardiac Surgery - Salem, Mohamed; Mohammad, Baland; Huenges, Katharina; Friedrich, Christine; Panholzer, Bernd; Cremer, Jochen; Hanyea, Assad (The Thoracic and Cardiovascular Surgeon, 2020)
Background Incidentally discovered severe calcified ascending aorta (CAA) is a major challenge faced by surgeons during cardiac surgery. The aim of this study was to evaluate the outcome in patients undergoing cardiac surgery in this condition with the additional replacement of the CAA.Methods A retrospective study on a cohort of 74 patients (28.4% females; mean age: 73 ± 7 years) underwent cardiac surgery and initial replacement of an incidentally discovered CAA using moderate hypothermic circulatory arrest. A control group was matched according to age, gender, and procedure.Results No significant differences were noted with regard to preoperative risk factors. Due to the additional replacement of CAA, the extracorporeal circulation and cross-clamping time were significantly longer in the study group (p < 0.001). Postoperatively, no significant differences in complications were observed between the groups. There was no significant difference in regard to incidence of neurologic adverse events (5.4 vs. 2.7%; p = 0.68) or 30-day mortality (6.7 vs. 4.1%; p = 0.72).Conclusion Our study showed that the initial replacement of incidental CAA in patients undergoing cardiac surgery was not associated with increased risks for neurologic adverse events and mortality.
Keywords: cardiac surgery; stroke; calcified ascending aorta; moderate hypothermic circulatory arrest